Response Surface Methodology Analysis of CO2 Photocatalytic Conversion in Presence of CH4 over Nitrogen-Doped Titania Nanotube Arrays - S. Delavari; N.A.S. Amin (Chemical Engineering Transactions, 2014)
Recently, in the research of photocatalytic conversion of CO2, there has been an increasing innovative interest to simultaneously reduce the level of CO2 emissions and produce valuable products. In this study, highly ordered nitrogen-doped titania (TiO2) nanotube arrays, fabricated by anodization method, were used for CO2 reduction in the presence of CH4. Response surface methodology (RSM) was employed to assess individual and interactive effects of UV light power, CO2:CH4:N2 ratios in feed and distance between the UV lamp and the reactor on CO2 conversion. A face-centered central composite design (FCCCD) was utilized to optimize the photocatalytic process conditions. The optimal conditions for maximum CO2 conversion of 41.5 % were determined as 250 W UV light power, 10 % CO2 initial ratio and 2 cm distance between UV lamp and reactor.